Implementation on the dSPACE 1104 of VOC-SVM based anti-windup PI Controller of a three-phase PWM rectifier - J. lamterkati; L. Ouboubker; M. Khafallah; A. El afia (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The study made in this paper concerns the use of the voltage-oriented control (VOC) of three-phase pulse width modulation (PWM) rectifier with constant switching frequency. This control method, called voltage-oriented controlwith space vector modulation (VOC-SVM). The proposed control scheme has been founded on the transformation between stationary (α-β) and and synchronously rotating (d-q) coordinate system, it is based on two cascaded control loops so that a fast inner loop controls the grid current and an external loop DC-link voltage, while the DC-bus voltage is maintained at the desired level and ansured the unity power factor operation. So, the stable state performance and robustness against the load’s disturbance of PWM rectifiers are boths improved. The proposed scheme has been implemented and simulated in MATLAB/Simulink environment. The control system of the VOC-SVM strategy has been built based on dSPACE system with DS1104 controller board. The results obtained show the validity of the model and its control method. Compared with the conventional SPWM method, the VOC-SVM ensures high performance and fast transient response.